IMPROVING STUDENTS’ SPEAKING FLUENCY IN PRIVATE CLASS: A CLASROOM ACTION RESEARCH - Yorina An’guna Bansa (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
After knowing the positive effects from what have been done and the students’ problem tospeak English, the teacher did a problem-solving for that English private class. To identify topic,researcher can reflect on their daily professional lives and ask herself, Here, the teacher gave asmuch as tutees can speak more often in this English private group. It is fascinated to observe howimprove students’ fluency to speak English. After watching the students’ condition and the students’problem, so the teacher used reporting technique to improve the students’ speaking fluency.Reporting technique gives opportunity for them to report about the free topic that they were interestedin. Students were less of fluency when speaking English. So, how did tutor improve students’ fluencyto speak English as a target language? This research will answer this question. The design of thisresearch was descriptive qualitative. There has been an improvement of students speaking fluency inthis English private group. By conducting this research, the teacher solved the students’ problems, theclassroom’s problem. For nine meetings, the teacher motivated, guided, and gave opportunities thestudents to practice English speaking more often. As a result, the students speaking fluencyimproved. The teacher should limit the use of first language in classroom interaction and alsomotivate them that improve their fluency of speaking English is greatly needed.Keywords: Classroom Action Research, ELT Contexts, Private Class, Students’ Speaking Fluency